Making MECC Work: Enhancing the implementation of the National Making Every Contact Count Programme in Ireland - Hayes, Catherine (University of Galway, 2022)
Increasing chronic disease is a key societal challenge: Rapidly increasing rates of chronic disease are a key global societal challenge; The successful prevention and management of chronic disease is critically important to population health and to the long-term effectiveness of the health service. Changing health-related behaviours is part of the solution: Changing health-related behaviours (including smoking, poor diet, excessive alcohol consumption and physical inactivity) can significantly reduce chronic disease. Brief behavioural interventions delivered by health professionals can support people to modify their health behaviour.
PUBLISHED
Keywords: Inclusive Society; Public health